The Effect of Teacher Training Programs on Chemistry Teachers' Readiness to Use ICTs in Teaching: A case study of Vietnamese New In-service Chemistry Teachers - Nguyen, Trang (My University, 2023)
Despite the widespread recognition of the TPACK and SAMR models as invaluable frameworks for integrating technology into teaching, Vietnamese teachers exhibit limited awareness and knowledge of these models. The research on teacher training in the country is also inadequate. This study aimed to address these gaps by investigating the levels of knowledge and current usage of technology among new in-service Chemistry teachers in Vietnam, using a TPACK-SAMR lens. The research questions focused on teachers' digital skills, perceptions of their teacher preparation program, and digital readiness for future technology integration. Data collection involved TPACK self-reported surveys, technology use frequency surveys, and individual interviews to gather further insights. The findings revealed that teachers exhibited high confidence in their digital skills, with the lowest confidence in Technological Content Knowledge (TCK). They frequently used technology, primarily at the Substitution and Augmentation levels of the SAMR model. However, the teacher training program needed to be improved, with recommendations for more hands-on exercises, peer collaboration, and a focus on commonly used educational technologies. The study's conclusions emphasize the need for teacher training programs to prioritize the development of TCK, implement effective practices such as work sample analysis and reflection, and encourage peer collaboration and networking opportunities between pre-service and in-service teachers. These findings contribute to the existing knowledge by highlighting areas for improvement in teacher training programs to enhance technology integration in Chemistry teaching.
Keywords: TPACK, SAMR, Teacher training, Educational technology, Chemistry education